2016
DOI: 10.1186/s13054-016-1340-3
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome and toll-like receptor signaling in human monocytes after successful cardiopulmonary resuscitation

Abstract: BackgroundWhole body ischemia-reperfusion injury (IRI) after cardiopulmonary resuscitation (CPR) induces a generalized inflammatory response which contributes to the development of post-cardiac arrest syndrome (PCAS). Recently, pattern recognition receptors (PRRs), such as toll-like receptors (TLRs) and inflammasomes, have been shown to mediate the inflammatory response in IRI. In this study we investigated monocyte PRR signaling and function in PCAS.MethodsBlood samples were drawn in the first 12 hours, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 63 publications
(33 reference statements)
3
40
0
Order By: Relevance
“…High levels of IL‐1 and catecholamine were observed in patients after cardiac arrest and resuscitation . Furthermore, IL‐1 mRNA expression and its protein production by monocytes was confirmed in these patients . Extremely high levels of adrenaline, approximately 2700 times greater than the normal range, may occur because of exogenous administration of adrenaline during CPR .…”
Section: Inflammation and Coagulationmentioning
confidence: 81%
See 1 more Smart Citation
“…High levels of IL‐1 and catecholamine were observed in patients after cardiac arrest and resuscitation . Furthermore, IL‐1 mRNA expression and its protein production by monocytes was confirmed in these patients . Extremely high levels of adrenaline, approximately 2700 times greater than the normal range, may occur because of exogenous administration of adrenaline during CPR .…”
Section: Inflammation and Coagulationmentioning
confidence: 81%
“…Monocytes purified from the blood of patients after cardiac arrest and resuscitation showed upregulation of TLR2, TLR4, IRAK4, and NLRP3 mRNAs from the early period (~12 hours) to the late period (~48 hours) after emergency department (ED) admission . In the early period, the serum lactate level, which is a surrogate marker of ischemia, is positively correlated with monocyte expression of TLR2, TLR4, and IRAK4.…”
Section: Inflammation and Coagulationmentioning
confidence: 99%
“…In other words, it may be hypothesized that some known or unknown factors may determine the main roles played by the inflammasomes during HCC. For example, participation, or not, of other innate immunity pathways such as TLRs, may be considered as the important reason for the involvement of the inflammasomes in the HCC protection or progression because of their roles in the production of priming signals [28,30]. Previous investigations showed that microRNA223 has anti-cancerous properties [86,87].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 99%
“…Additionally, ATP binding to the purinergic receptor P2 × 7 and activation of cathepsins result in activation of the inflammasomes [26][27][28][29]. There is some evidence which demonstrated that inflammasomes need priming signals to be activated by the ligands [28,30]. The priming signals are derived from other innate immunity receptors such as toll-like receptors (TLRs) [28,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation